Release behavior of uranium from a uranium tailing in Jiangxi Province - Xue, Shiqi; Wang, Zili; Ouyang, Jinbo; Zhou, Limin; Liu, Zhirong (Frontiers in Environmental Science, 2022)
In this study, nine soils at different depths in a decommissioned uranium tailing pond in Jiangxi Province are selected as the research objects to study their mineralogical properties and reveal the leaching law of radioactive element uranium under natural rainfall conditions. The research results are as follows: (1) The distribution characteristics of uranium are affected by the mineral composition, microscopic morphology and physical and chemical properties of uranium tailings. (2) In static leaching experiments, acidic solutions, small particles, and high solid-to-liquid ratios all promote the release of uranium. (3) In the dynamic leaching experiment, the lower the pH of simulated rainfall, the more uranium is released. According to Fick theory, the migration mechanism of uranium is mainly surface dissolution, and the release of uranium is related to the content of migratory uranium.